The emotional politics of the alternative left : West Germany, 1968-1984 - Häberlen, Joachim C. 1980- (New studies in European history, 2018)
"In the 1970s, a multifaceted alternative scene developed in West Germany. At the core of this leftist scene was a struggle for feelings in a capitalist world that seemed to be devoid of any emotions. Joachim C. Häberlen offers a vivid account of these emotional politics. The book discusses critiques of rationality and celebrations of insanity as an alternative. It explores why capitalism made people feel afraid and why modern cities made people feel lonely. Readers are taken to consciousness raising groups, nude swimming at alternative vacation camps, and into the squatted houses of the early 1980s. Häberlen draws on a kaleidoscope of different voices to explore how West Germans became more concerned with their selves, their feelings and their bodies. By investigating how leftists tried to transform themselves through emotional practices, Häberlen gives us a fresh perspective on a fascinating aspect of West German history."--